Current Assessment Practices A Report from the Virginia Assessment Study Group. - Virginia Adult Educators Research Network, Dayton; Virginia Adult Educators Research Network, Dayton ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1997)
The report details the activities of the Virginia Assessment Study Group in documenting the utility of various approaches to assessing adult education programs and instruction within the state. A group of diverse practitioners convened during 1997 to establish project objectives and research questions and to report on their work. The reports of seven group members, all adult education teachers, concerning a variety of assessment procedures are presented here. The members bring experience from the fields of adult basic education, English as a second language (ESL), correctional education, social services, and family literacy programming. Reports include information about the types of learners and classes involved, the physical setting, class schedules, enrollment procedures, and relevant employment situations. Recommendations for assessment practices and for future study groups emerging from the project are also presented. (Contains 102 references.) (MSE) (Adjunct ERIC Clearinghouse on Literacy Education)
Sponsoring Agency: Department of Education, Washington, DC.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Adult Basic Education; Adult Education; Correctional Education; English (Second Language); Evaluation Criteria; Evaluation Methods; Family Programs; Instructional Effectiveness; Literacy Education; Program Effectiveness; Program Evaluation; Second Language Instruction; Student Evaluation; Reports, Descriptive